The relationship between blood glucose and clinical outcomes after extracorporeal circulation: a retrospective cohort study - Li Li; Li Li; Rui Li; Yi-Jiang Liu; Zhan Wang; Xin Chen; Lin-Xi Xu; Lin-Xi Xu; Zhi-Huang Chen; Jia-Cheng Xu; Zhong-Gui Shan; Zhong-Gui Shan (Frontiers in Cardiovascular Medicine)
BackgroundPostoperative blood glucose levels significantly impact outcomes in cardiac surgery patients undergoing extracorporeal circulation (ECC) auxiliary to open heart surgery. While hypoglycemia and hyperglycemia are known risk factors for adverse outcomes, the optimal glycemic range for patients undergoing ECC remains unclear. This research examined the relationship between blood glucose levels and 90-day mortality in this high-risk group.MethodsThe data for this research were obtained from the Medical Information Mart for Intensive Care-IV database version 2.2(MIMIC-IV 2.2), including 4,033 patients who underwent ECC-assisted open-heart surgery. Patients were classified into quartiles based on blood glucose values measured within a 24 h period following admission to the ICU. The study's primary outcome was the 90-day mortality, and the duration of hospital and ICU stays were considered secondary outcomes. Kaplan–Meier survival analysis, Multivariate Cox regression models, smooth curve fitting, Restricted Cubic Spline (RCS) curve, and subgroup analyses were conducted to evaluate the relationship between blood glucose levels and patient outcomes.ResultsHigher blood glucose levels were significantly related to increased 90-day mortality. The analysis revealed the nonlinear relation between blood glucose and 90 days mortality, with an inflection point at 119 mg/dl (P < 0.05). Patients with blood glucose levels above this threshold had a markedly higher risk of mortality. Additionally, elevated blood glucose was associated with prolonged hospitalization and ICU stays.ConclusionElevated postoperative blood glucose values were related to an increased 90-day mortality in patients who underwent ECC. When blood glucose levels exceeded 119 mg/dl, blood glucose levels were positively associated with 90-day postoperative mortality.